High‐frequency temperature monitoring with time‐resolved wavelet analysis reveals unrecognized complexities across depth on a coral reef ecosystem - Aubrey Foulk; Tarik Gouhier; James Leichter; Alex S. J. Wyatt; Randi Rotjan; Mark Patterson; Brian Helmuth (Limnology and Oceanography, 2026)
Temperature variation at fine scales of minutes to hours and ~ 1–100 m is ubiquitous in marine ecosystems and often exceeds variability at larger scales. However, we know little of how well temperatures at one location or depth can serve as proxies to represent other locations, which is important in predicting thermal patterns relevant to organismal thermal stress. We used small data loggers to record fine‐scale temporal variability in water temperature across a depth gradient, over multiple years, on the barrier reef system in Belize. Using pairwise correlation and wavelet coherence, which quantifies the time‐ and frequency‐resolved correlation between pairs of time series, we examine how water temperature varies across reef zones (backreef, forereef inner, and forereef outer) and depths, and estimate the coherence of this variability across time scales. Although spectral analysis across the entire study period suggested a high degree of similarity in temperature patterns, time‐resolved wavelet analyses at daily, weekly, and monthly periodicities revealed significant differences across reef‐zone‐by‐depth combinations. We also detected a signal consistent with the Madden–Julian Oscillation. Coherence and phase locking at biologically relevant periodicities diminished with increasing depth difference between sites, suggesting that patterns at depth were not predictable from those near the surface. Overall, our findings show that wavelet analysis can reveal fine‐scale thermal variation on coral reefs that coarser sampling misses, and they make clear that accurately predicting how organismal performance will shift in space and time under global change depends on collecting and analyzing depth‐resolved, high‐frequency, in situ data wherever possible.

Ancestry informative genetic variants associated with tobacco metabolic and detoxification capacity measured by 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) among smokers - Oladimeji Lanade; Zhongxuan He; Yan Zhou; Elizabeth Blackman; Denise Gibbs; Sharon Harrison; Karthik Devarajan; Mark Andrake; Roland L. Dunbrack; Gerald Nkogbu; Aditi Wagh; Michael Slifker; et al. (Archives of Toxicology, 2026)
Tobacco use remains the leading preventable cause of cancer mortality worldwide, with marked disparities in cancer incidence and outcomes across racial and ethnic groups. This study investigates the genetic determinants of tobacco carcinogen metabolism among smokers, focusing on ancestry-informative markers (AIMs) near genes involved in metabolic activation (Phase I), detoxification (Phase II), and transport (Phase III) of tobacco-specific carcinogens. Using data from 274 smokers recruited in the United States and the Caribbean, we measured urinary NNAL (a metabolite of NNK) to classify metabolic phenotypes and performed genotyping with a customized array enriched for AIMs. Most participants (94%) were classified as poor metabolizers of NNAL, with a higher prevalence among Black/African American smokers. Multivariable analyses, after adjusting for age, sex, assay batch, and number of cigarettes smoked per day, identified 14 AIMs near Phase I, II, and III pathway genes significantly associated with NNAL metabolizer phenotype, with African ancestry alleles conferring increased odds of poor metabolism. Functional annotation revealed that most significant AIMs overlapped regulatory regions, and the CYP3A5 rs776746 variant demonstrated structural disruption likely to impair enzymatic activity. Majority of participants had high African ancestry and were poor NNAL metabolizers, consistent with the observed association between African ancestry and poor NNAL metabolism. These findings highlight the biological basis for tobacco-related cancer disparities and underscore the importance of integrating genetic ancestry and metabolic phenotyping in risk assessment and personalized prevention strategies for tobacco-associated cancers.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Challenges and solutions in measuring commonly used biomarkers for drug-induced liver injury in a liver-on-a-chip platform - Qiang Shi; Laura K. Schnackenberg; Lijun Ren; Katy S. Papineau; Jessica J.H. Oliphant; Mark I. Avigan; Lorna Ewart; John FK. Sauld; Emily Dai; Paul C. Brown; Karen L. Davis Bruno; Frederic Moulin; et al. (Toxicology Letters, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Corrigendum: Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2025)

Predicting and assessing the impacts of COVID-19 disruption on marine science and sectors in Australia - Alistair J. Hobday; Vicki M. Walters; Robert L. Stephenson; Shane Baylis; Cindy Bessey; Fabio Boschetti; Catherine Bulman; Stephanie Contardo; Jeffrey M. Dambacher; Jemery Day; Natalie A. Dowling; Piers Dunstan; et al. (Reviews in Fish Biology and Fisheries, 2025)
By March 2020 coronavirus disease 2019 (COVID-19) was anticipated to present a major challenge to the work undertaken by scientists. This pandemic could be considered just one of the shocks that human society has had and will be likely to confront again in the future. As strategic thinking about the future can assist performance and planning of scientific research in the face of change, the pandemic presented an opportunity to evaluate the performance of marine researchers in prediction of future outcomes. In March 2020, two groups of researchers predicted outcomes for the Australian marine research sector, and then evaluated these predictions after 18 months. The self-assessed coping ability of a group experienced in ‘futures studies’ was not higher than the less-experienced group, suggesting that scientists in general may be well placed to cope with shocks. A range of changes to scientific endeavours (e.g., travel, fieldwork) and to marine sectors (e.g., fisheries, biodiversity) were predicted over the first 12–18 months of COVID-19 disruption. The predicted direction of change was generally correct (56%) or neutral (25%) for predictions related to the scientific endeavour, and correct (73%) or mixed (9%) for predictions related to sectors that are the focus of marine research. The success of this foresighting experiment suggests that the collective wisdom of scientists can be used by their organisations to consider the impact of shocks and disruptions and to better prepare for and cope with shocks. Graphical abstract Word cloud analysis of free text responses to questions about expected impact of COVID-19 on the activities associated with marine science

The effects of exercise, heat-induced hypo-hydration and rehydration on blood–brain-barrier permeability, corticospinal and peripheral excitability - Nasir Uddin; Jamie Scott; Jonathan Nixon; Stephen D. Patterson; Dawson Kidgell; Alan J. Pearce; Mark Waldron; Jamie Tallent (European Journal of Applied Physiology, 2025)
Purpose The effects of low-intensity exercise, heat-induced hypo-hydration and rehydration on maximal strength and the underlying neurophysiological mechanisms are not well understood. Methods To assess this, 12 participants took part in a randomised crossover study, in a prolonged (3 h) submaximal (60 W) cycling protocol under 3 conditions: (i) in 45 °C (achieving ~ 5% body mass reduction), with post-exercise rehydration in 2 h (RHY2), (ii) with rehydration across 24 h (RHY24), and (iii) a euhydrated trial in 25 °C (CON). Dependent variables included maximal voluntary contractions (MVC), maximum motor unit potential (M MAX ), motor evoked potential (MEP RAW ) amplitude and cortical silent period (cSP) duration. Blood–brain-barrier integrity was also assessed by serum Ubiquitin Carboxyl-terminal Hydrolase (UCH-L1) concentrations. All measures were obtained immediately pre, post, post 2 h and 24 h. Results During both dehydration trials, MVC (RHY2: p < 0.001, RHY24: p = 0.001) and MEP RAW (RHY2: p = 0.025, RHY24: p = 0.045) decreased from pre- to post-exercise. MEP RAW returned to baseline during RHY2 and CON, but not RHY24 ( p = 0.020). MEP/M MAX ratio decreased across time for all trials ( p = 0.009) and returned to baseline, except RHY24 ( p < 0.026). Increased cSP ( p = 0.011) was observed during CON post-exercise, but not during RHY2 and RHY24. Serum UCH-L1 increased across time for all conditions ( p < 0.001) but was not significantly different between conditions. Conclusion Our findings demonstrate an increase in corticospinal inhibition after exercise with fluid ingestion, but a decrease in corticospinal excitability after heat-induced hypo-hydration. In addition, low-intensity exercise increases peripheral markers of blood–brain-barrier permeability. Graphical abstract

Drivers of Interspecific Spatial Segregation in Two Closely‐Related Seabird Species at a Pan‐Atlantic Scale - Anne‐Sophie Bonnet‐Lebrun; Jason Matthiopoulos; Rémi Lemaire‐Patin; Tanguy Deville; Robert Barrett; Maria I. Bogdanova; Mark Bolton; Signe Christensen‐Dalsgaard; Francis Daunt; Nina Dehnhard; Sébastien Descamps; Kyle Elliott; et al. (Journal of Biogeography, 2025)
Aim Ecologically similar species living in sympatry are expected to segregate to reduce the effects of competition where resources are limiting. Segregation from heterospecifics commonly occurs in space, but it is often unknown whether such segregation has underlying environmental causes. Indeed, species could segregate because of different fundamental environmental requirements (i.e., ‘niche divergence’), because competitive exclusion at sympatric sites can force species to either change the habitat use they would have at allopatric sites (i.e., ‘niche displacement’) or to avoid certain areas, independently of habitat (i.e., ‘spatial avoidance’). Testing these hypotheses requires the comparison between sympatric and allopatric sites. Understanding the competitive mechanisms that underlie patterns of spatial segregation could improve predictions of species responses to environmental change, as competition might exacerbate the effects of environmental change. Location North Atlantic and Arctic. Taxa Common guillemots Uria aalge and Brünnich's guillemots Uria lomvia. Methods Here, we examine support for these explanations for spatial segregation in two closely‐related seabird species, common guillemots ( Uria aalge ) and Brünnich's guillemots ( U. lomvia ). For this, we collated a pan‐Atlantic data set of breeding season foraging tracks from 1046 individuals, collected from 20 colonies (8 sympatric and 12 allopatric). These were analysed with habitat models in a spatially transferable framework to compare habitat preferences between species at sympatric and allopatric sites. Results We found no effect of the distribution of heterospecifics on local habitat preferences of the focal species. We found differences in habitat preferences between species, but these were not sufficient to explain the observed levels of spatial segregation at sympatric sites. Main Conclusions Assuming we did not omit any relevant environmental variables, these results suggest a mix of niche divergence and spatial avoidance produces the observed patterns of spatial segregation.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

Restoration of herbivory on Caribbean coral reefs: are fishes, urchins, or crabs the solution? - Mark J. Butler; Alain Duran; Colette J. Feehan; Alastair R. Harborne; Alwin Hylkema; Joshua T. Patterson; William C. Sharp; Angelo Jason Spadaro; Tom Wijers; Stacey M. Williams (Frontiers in Marine Science, 2024)
That coral reefs are in decline worldwide, particularly in the Caribbean, will come as no surprise. This decades-long decline has reached a potential tipping point as the weight of the effects of climate change have come decidedly to bear on the planet’s most diverse marine ecosystem. Whether coral reefs can persist without restorative intervention is debatable, which has prompted a surge in coral reef restoration projects focusing primarily on the cultivation and transplantation of coral fragments onto degraded reefs. But that widespread approach does little to address the underlying causes of coral loss, one of which is the proliferation of macroalgae that are deleterious to corals. An emerging solution to this problem is the enhancement of herbivory on coral reefs through improved management of herbivores, artificial enhancement of herbivore settlement, or their mariculture and subsequent stocking. This review explores the nuances of the biology of well-studied Caribbean coral reef herbivores (fishes, sea urchins, and crabs) as it relates to their mariculture and investigates the promise of herbivore stocking onto coral reefs as a restoration strategy. Fish, urchin, and crab herbivores differ appreciably in life histories, which confers advantages and disadvantages with respect to their mariculture and effectiveness as grazers. Mariculture of herbivorous marine fish for reef restoration is essentially non-existent so the reestablishment of grazing fish abundance on coral reefs focuses primarily on their protection through fishery regulations, but only at a few locations in the Caribbean. Mariculture of herbivorous urchins and crabs for restoration purposes is in its infancy, but promising especially for crabs whose larval rearing is less difficult. Perhaps the biggest challenge for the mariculture of either taxon is “scaling-up” from research settings to large-scale mariculture needed for stocking. Numerous studies extol the benefits of functional redundancy and complementarity for coral reef ecosystem stability, but whether this principal applies to the restoration of grazing function is untested. We identify gaps in our knowledge of best practices for the restoration of grazing function on coral reefs and conclude with some practical guidance on the establishment of targets for macroalgal reduction, along with strategic advice on grazer stocking in a given reef habitat.

Spatial distribution of selenium-mercury in Arctic seabirds - Marta Cruz-Flores; Jérémy Lemaire; Maud Brault-Favrou; Signe Christensen-Dalsgaard; Carine Churlaud; Sébastien Descamps; Kyle Elliott; Kjell Einar Erikstad; Alexey Ezhov; Maria Gavrilo; David Grémillet; Gaël Guillou; et al. (Environmental Pollution, 2024)

Microscale flow dynamics and particle capture in scleractinian corals: I. Role of the tentacles - Wm. Stephen Price; Mark R. Patterson (Coral Reefs, 2023)
The size, shape, and arrangement of tentacles in scleractinian coral polyps are likely to affect particle capture yet have not been investigated in a systematic way. Morphometric measurements of tentacles of several coral species found in the Caribbean Sea were taken from macro-photographs, and from these, models were constructed in three postures: straight, upstream-facing, and downstream-facing. These models were placed in a flume to video the flow paths of particles around them. Video analysis indicates tentacles, and their specific postures, have a dramatic effect on micro-flow patterns. The expanded soft tissue tentacles, and their specific postures, greatly increase probability of particle capture by direct impaction, inertial impaction, and gravitational deposition. All tentacle postures cause increased retention time relative to freestream travel in their immediate proximity, as well as increasing both contact with the tentacle surface, and tumbling of particles. Straight and upstream-facing tentacles deflect particles downward to their base, while downstream-facing tentacles deflect particles upwards. When results from individual tentacles are considered in geometric combination, the secondary radial symmetry of the tentacular whorls in simple coral polyps appears to be an optimal strategy to filter suspended particulate material in an oscillating and omni-directional flow environment. In meandrine corals, the hedgerows of straight and curved tentacles appear to draw particles downward, retain them, and direct them onto the oral feeding areas below the thecal ridges. The size, shape, and arrangement of tentacles are thus of key importance in understanding suspension feeding in scleractinian corals.

Corrigendum to “Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification” [Biol. Conserv. 281 (2023) 109994] - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Quantifying annual spatial consistency in chick-rearing seabirds to inform important site identification - Martin Beal; Paulo Catry; Richard A. Phillips; Steffen Oppel; John P.Y. Arnould; Maria I. Bogdanova; Mark Bolton; Ana P.B. Carneiro; Corey Clatterbuck; Melinda Conners; Francis Daunt; Karine Delord; et al. (Biological Conservation, 2023)

Improving certainty in marine ecosystems: A biophysical modelling approach in the remote, data-limited Gulf of Carpentaria - Ruth G. Patterson; Eric Wolanski; Rachel Groom; Kay Critchell; Luke Playford; Mark Grubert; Rod Kennett; Heidi Tait; Vinay Udyawer; Jonathan Lambrechts; Hamish A. Campbell (Estuarine, Coastal and Shelf Science, 2023)

Sea-level changes and paleoenvironmental responses in a coastal Florida salt marsh over the last three centuries - Carina Seitz; William F. Kenney; Brittany Patterson-Boyarski; Jason H. Curtis; María I. Vélez; Katie Glodzik; Jaime Escobar; Mark Brenner (Journal of Paleolimnology, 2023)

Corticospinal and peripheral responses to heat-induced hypo-hydration: potential physiological mechanisms and implications for neuromuscular function - Nasir Uddin; Jamie Tallent; Stephen D. Patterson; Stuart Goodall; Mark Waldron (European Journal of Applied Physiology, 2022)
Heat-induced hypo-hydration (hyperosmotic hypovolemia) can reduce prolonged skeletal muscle performance; however, the mechanisms are less well understood and the reported effects on all aspects of neuromuscular function and brief maximal contractions are inconsistent. Historically, a 4–6% reduction of body mass has not been considered to impair muscle function in humans, as determined by muscle torque, membrane excitability and peak power production. With the development of magnetic resonance imaging and neurophysiological techniques, such as electromyography, peripheral nerve, and transcranial magnetic stimulation (TMS), the integrity of the brain-to-muscle pathway can be further investigated. The findings of this review demonstrate that heat-induced hypo-hydration impairs neuromuscular function, particularly during repeated and sustained contractions. Additionally, the mechanisms are separate to those of hyperthermia-induced fatigue and are likely a result of modulations to corticospinal inhibition, increased fibre conduction velocity, pain perception and impaired contractile function. This review also sheds light on the view that hypo-hydration has ‘no effect’ on neuromuscular function during brief maximal voluntary contractions. It is hypothesised that irrespective of unchanged force, compensatory reductions in cortical inhibition are likely to occur, in the attempt of achieving adequate force production. Studies using single-pulse TMS have shown that hypo-hydration can reduce maximal isometric and eccentric force, despite a reduction in cortical inhibition, but the cause of this is currently unclear. Future work should investigate the intracortical inhibitory and excitatory pathways within the brain, to elucidate the role of the central nervous system in force output, following heat-induced hypo-hydration.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

A first genetic assessment of the newly introduced Isle Royale gray wolves (Canis lupus) - Samuel D. Hervey; Linda Y. Rutledge; Brent R. Patterson; Mark C. Romanski; John A. Vucetich; Jerrold L. Belant; Dean E. Beyer; Seth A. Moore; Kristin E. Brzeski (Conservation Genetics, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Correction to: Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Modification of the third phase in the framework for vertebrate species persistence in urban mosaic environments - Colleen T. Downs; Jarryd Alexander; Mark Brown; Moses Chibesa; Yvette C. Ehlers Smith; S. Thobeka Gumede; Lorinda Hart; Kyrone K. Josiah; Riddhika Kalle; Machawe Maphalala; Mfundo Maseko; Shane McPherson; et al. (Ambio, 2021)

Illuminating the Past to See the Future of Western Boundary Currents: Micropaleontological Investigations of the Kuroshio Current Extension - Adriane Lam; Mark Leckie; Molly Patterson (Oceanography, 2020)

Resistance and robustness of the global coral–symbiont network - Sara D. Williams; Mark R. Patterson (Ecology, 2020)
Increasing ocean temperatures have widespread consequences for coral reefs, one of which is coral bleaching. We analyzed a global network of associations between coral species and Symbiodiniaceae for resistance to temperature stress and robustness to perturbations. Null networks were created by changing either the physiological parameters of the nodes or the structures of the networks. We developed a bleaching model in which each link, association, is given a weight based on temperature thresholds for specific host–symbiont pairs and links are removed as temperature increases. Resistance to temperature stress was determined from the response of the networks to the bleaching model. Ecological robustness, defined by how much perturbation is needed to decrease the number of nodes by 50%, was determined for multiple removal models that considered traits of the hosts, symbionts, and their associations. Network resistance to bleaching and robustness to perturbations differed from the null networks and varied across spatial scales, supporting that thermal tolerances, local association patterns, and environment play an important role in network persistence. Networks were more robust to attacks on associations than to attacks on species. Although the global network was fairly robust to random link removals, when links are removed according to the bleaching model, robustness decreases by about 20%. Specific environmental attacks, in the form of increasing temperatures, destabilize the global network of coral species and Symbiodiniaceae. On a global scale, the network was more robust to removals of links with susceptible Symbiodiniaceae than it was to removals of links with susceptible hosts. Thus, the symbionts convey more stability to the symbiosis than the hosts when the system is under an environmental attack. However, our results also provide evidence that the environment of the networks affects robustness to link perturbations. Our work shows that ecological resistance and robustness can be assessed through network analysis that considers specific biological traits and functional weaknesses. The global network of associations between corals and Symbiodiniaceae and its distribution of thermal tolerances are non‐random, and the evolution of this architecture has led to higher sensitivity to environmental perturbations.

The time course of adaptations in thermoneutral maximal oxygen consumption following heat acclimation - Mark Waldron; O. Jeffries; J. Tallent; S. Patterson; V. Nevola (European Journal of Applied Physiology, 2019)
Purpose This study investigated the effects of a 10-day heat acclimation (HA) programme on the time course of changes in thermoneutral maximal oxygen uptake ( $$\dot{V}$$ V ˙ O 2max ) during and up to 10 days post-HA. Methods Twenty-two male cyclists were assigned to a HA or control (Con) training group following baseline ramp tests of thermoneutral $$\dot{V}$$ V ˙ O 2max . Ten days of fixed-intensity (50% baseline $$\dot{V}$$ V ˙ O 2max ) indoor cycling was performed in either ~ 38.0 °C (HA) or ~ 20 °C (Con). $$\dot{V}$$ V ˙ O 2max was re-tested on HA days 5, 10 and post-HA days 1, 2, 3, 4, 5 and 10. Results $$\dot{V}$$ V ˙ O 2max initially declined across time in both groups during training ( P < 0.05), before increasing in the post-HA period in both groups ( P < 0.05). However, $$\dot{V}$$ V ˙ O 2max was higher than control by post-HA day 4 in the HA group ( P = 0.046). Conclusions The non-linear time course of $$\dot{V}$$ V ˙ O 2max adaptation suggests that post-testing should be performed 96-h post-training to identify the maximal change for most individuals. In preparation for training or testing, athletes can augment their aerobic power in thermoneutral environments by performing 10 days HA, but the full effects will manifest at varying stages of the post-HA period.

The effect of severe and moderate hypoxia on exercise at a fixed level of perceived exertion - Owen Jeffries; Stephen David Patterson; Mark Waldron (European Journal of Applied Physiology, 2019)

Temporal and spatial differences in smolting among Oncorhynchus nerka populations throughout fresh and seawater migration - Marley C. Bassett; David A. Patterson; J. Mark Shrimpton (Journal of Fish Biology, 2018)
Physiological changes that occur in the spring are preparatory for salmonid smolts to successfully enter seawater, but variation is likely to exist within species with a wide geographic distribution. Whether differences in development of seawater tolerance exist among populations that differ in distance to the ocean, temporally during the spring, or as fish migrate downstream is not known. Juvenile sockeye salmon Oncorhynchus nerka from four regions in the Fraser River catchment, British Columbia, were intercepted to assess physiological differences among populations and at different times during migration to characterize the parr–smolt transformation. Pre‐migratory fish had low levels of gill Na + –K + ‐ATPase (NKA) activity. High gill NKA activities were observed at the start of migration for some populations, but smolts leaving the lake did not consistently have higher gill NKA activity than non‐migratory juvenile O. nerka sampled in their natal lakes. Gill NKA activity was highly variable at the start of migration with no relationship with distance from the ocean. Gill NKA activity changes with migration were also highly variable, but consistently smolts in the ocean had the highest enzyme activities. Internal and external factors may influence this variation, but the dynamic nature of smolting was not based on the region of origin, timing during migration or on the year of migration.

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Ecosystem state shifts during long‐term development of an Amazonian peatland - Graeme T. Swindles; Paul J. Morris; Bronwen Whitney; Jennifer M. Galloway; Mariusz Gałka; Angela Gallego‐Sala; Andrew L. Macumber; Donal Mullan; Mark W. Smith; Matthew J. Amesbury; Thomas P. Roland; Hamed Sanei; et al. (Global Change Biology, 2018)
The most carbon (C)‐dense ecosystems of Amazonia are areas characterized by the presence of peatlands. However, Amazonian peatland ecosystems are poorly understood and are threatened by human activities. Here, we present an investigation into long‐term ecohydrological controls on C accumulation in an Amazonian peat dome. This site is the oldest peatland yet discovered in Amazonia (peat initiation ca. 8.9 ka BP ), and developed in three stages: (i) peat initiated in an abandoned river channel with open water and aquatic plants; (ii) inundated forest swamp; and (iii) raised peat dome (since ca. 3.9 ka BP ). Local burning occurred at least three times in the past 4,500 years. Two phases of particularly rapid C accumulation (ca. 6.6–6.1 and ca. 4.9–3.9 ka BP ), potentially resulting from increased net primary productivity, were seemingly driven by drier conditions associated with widespread drought events. The association of drought phases with major ecosystem state shifts (open water wetland–forest swamp–peat dome) suggests a potential climatic control on the developmental trajectory of this tropical peatland. A third drought phase centred on ca. 1.8–1.1 ka BP led to markedly reduced C accumulation and potentially a hiatus during the peat dome stage. Our results suggest that future droughts may lead to phases of rapid C accumulation in some inundated tropical peat swamps, although this can lead ultimately to a shift to ombrotrophy and a subsequent return to slower C accumulation. Conversely, in ombrotrophic peat domes, droughts may lead to reduced C accumulation or even net loss of peat. Increased surface wetness at our site in recent decades may reflect a shift towards a wetter climate in western Amazonia. Amazonian peatlands represent important carbon stores and habitats, and are important archives of past climatic and ecological information. They should form key foci for conservation efforts.

Mesophotic Coral Ecosystems: A Geoacoustically Derived Proxy for Habitat and Relative Diversity for the Leeward Shelf of Bonaire, Dutch Caribbean - Arthur C. Trembanis; Alexander L. Forrest; Bryan M. Keller; Mark R. Patterson (Frontiers in Marine Science, 2017)

How does the proliferation of the coral-killing sponge Terpios hoshinota affect benthic community structure on coral reefs? - Jennifer Elliott; Mark Patterson; Natalie Summers; Céline Miternique; Emma Montocchio; Eugene Vitry (Coral Reefs, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Morphological plasticity allows coral to actively overgrow the aggressive sponge Terpios hoshinota (Mauritius, Southwestern Indian Ocean) - Jennifer Elliott; Mark Patterson; Eugene Vitry; Natalie Summers; Céline Miternique (Marine Biodiversity, 2016)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Aquifer residence times for recycled water estimated using chemical tracers and the propagation of temperature signals at a managed aquifer recharge site in Australia - Elise Bekele; Bradley Patterson; Simon Toze; Andrew Furness; Simon Higginson; Mark Shackleton (Hydrogeology Journal, 2014)

Incorporating Climate and Ocean Change into Extinction Risk Assessments for 82 Coral Species - RUSSELL E. BRAINARD; MARISKA WEIJERMAN; C. MARK EAKIN; PAUL MCELHANY; MARGARET W. MILLER; MATT PATTERSON; GREGORY A. PINIAK; MATTHEW J. DUNLAP; CHARLES BIRKELAND (Conservation Biology, 2013)
Many marine invertebrate species facing potential extinction have uncertain taxonomies and poorly known demographic and ecological traits. Uncertainties are compounded when potential extinction drivers are climate and ocean changes whose effects on even widespread and abundant species are only partially understood. The U.S. Endangered Species Act mandates conservation management decisions founded on the extinction risk to species based on the best available science at the time of consideration—requiring prompt action rather than awaiting better information. We developed an expert‐opinion threat‐based approach that entails a structured voting system to assess extinction risk from climate and ocean changes and other threats to 82 coral species for which population status and threat response information was limited. Such methods are urgently needed because constrained budgets and manpower will continue to hinder the availability of desired data for many potentially vulnerable marine species. Significant species‐specific information gaps and uncertainties precluded quantitative assessments of habitat loss or population declines and necessitated increased reliance on demographic characteristics and threat vulnerabilities at genus or family levels. Adapting some methods (e.g., a structured voting system) used during other assessments and developing some new approaches (e.g., integrated assessment of threats and demographic characteristics), we rated the importance of threats contributing to coral extinction risk and assessed those threats against population status and trend information to evaluate each species’ extinction risk over the 21st century. This qualitative assessment resulted in a ranking with an uncertainty range for each species according to their estimated likelihood of extinction. We offer guidance on approaches for future biological extinction risk assessments, especially in cases of data‐limited species likely to be affected by global‐scale threats. Incorporación del Cambio Climático y Oceánico en Estudios de Riesgo de Extinción para 82 Especies de Coral

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Exertional thermal strain, protective clothing and auxiliary cooling in dry heat: evidence for physiological but not cognitive impairment - Joanne N. Caldwell; Mark J. Patterson; Nigel A. S. Taylor (European Journal of Applied Physiology, 2012)

Observations on saliva osmolality during progressive dehydration and partial rehydration - Nigel A. S. Taylor; Anne M. J. van den Heuvel; Pete Kerry; Sheena McGhee; Gregory E. Peoples; Marc A. Brown; Mark J. Patterson (European Journal of Applied Physiology, 2012)

Letting Penguins Lead: Dynamic Modeling of Penguin Locations Guides Autonomous Robotic Sampling - Matthew Oliver; Mark Moline; Ian Robbins; William Fraser; Donna Patterson; Oscar Schofield (Oceanography, 2012)

Effectiveness of short-term heat acclimation for highly trained athletes - Andrew T. Garrett; Rob Creasy; Nancy J. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2012)

Non-steroidal anti-inflammatory drugs and cancer incidence by sex in the VITamins And Lifestyle (VITAL) cohort - Theodore M. Brasky; John D. Potter; Alan R. Kristal; Ruth E. Patterson; Ulrike Peters; Maryam M. Asgari; Mark D. Thornquist; Emily White (Cancer Causes & Control, 2012)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Holocene climate and environmental change in central New York (USA) - Henry T. Mullins; William P. Patterson; Mark A. Teece; Adam W. Burnett (Journal of Paleolimnology, 2011)

Predicting feeding success in a migratory predator: integrating telemetry, environment, and modeling techniques - Sophie Bestley; Toby A. Patterson; Mark A. Hindell; John S. Gunn (Ecology, 2010)
Foraging theory predicts that mobile predators should target high profitability areas with plentiful resources and minimize time spent moving between these areas. This has led to a focus in recent literature on the identification of “hotspots” important for migratory marine predators, i.e., regions where predators spend disproportionate amounts of time ostensibly due to high prey abundance; and determination of the environmental features characteristic of such areas. We investigated factors predicting foraging success in southern bluefin tuna (SBT; Thunnus maccoyii ), by integrating telemetry‐based feeding and movement data ( n = 19 fish, length to caudal fork [LCF] = 99 ± 3 cm) with environmental data over the scale of their annual oceanic migrations during 1998–2000. We used widely available statistical modeling techniques, generalized linear models, and generalized linear mixed models, formulated to represent feeding as a Markov process. The results showed increased feeding and predictability of feeding occurs in the coastal waters of southern Australia, providing some evidence that this area represents a fixed foraging “hotspot” for juvenile tuna during the austral summer. However, in oceanic waters southern bluefin tuna did not fit the common model of migration, but rather showed a pattern of relatively high foraging success throughout their migratory range, especially during periods of continuous travel. Interestingly, foraging “coldspots” (prolonged low‐feeding periods) as well as “hotspots” were apparent across individual tracks, predicted most strongly by warm ocean temperatures. These results provide a new perspective on the ecology of large‐scale feeding migrations within the context of the heterogeneous ocean environment, where the continuous and opportunistic feeding of generalist predators may be more common, particularly in predatory large pelagic fishes, than is currently documented.

Using GPS data to evaluate the accuracy of state–space methods for correction of Argos satellite telemetry error - Toby A. Patterson; Bernie J. McConnell; Mike A. Fedak; Mark V. Bravington; Mark A. Hindell (Ecology, 2010)
Recent studies have applied state–space models to satellite telemetry data in order to remove noise from raw location estimates and infer the true tracks of animals. However, while the resulting tracks may appear plausible, it is difficult to determine the accuracy of the estimated positions, especially for position estimates interpolated to times between satellite locations. In this study, we use data from two gray seals ( Halichoerus grypus ) carrying tags that transmitted Fastloc GPS positions via Argos satellites. This combination of Service Argos data and highly accurate GPS data allowed examination of the accuracy of state–space position estimates and their uncertainty derived from satellite telemetry data. After applying a speed filter to remove aberrant satellite telemetry locations, we fit a continuous‐time Kalman filter to estimate the parameters of a random walk, used Kalman smoothing to infer positions at the times of the GPS measurements, and then compared the filtered telemetry estimates with the actual GPS measurements. We investigated the effect of varying maximum speed thresholds in the speed‐filtering algorithm on the root mean‐square error (RMSE) estimates and used minimum RMSE as a criterion to guide the final choice of speed threshold. The optimal speed thresholds differed between the two animals (1.1 m/s and 2.5 m/s) and retained 50% and 65% of the data for each seal. However, using a speed filter of 1.1 m/s resulted in very similar RMSE for both animals. For the two seals, the RMSE of the Kalman‐filtered estimates of location were 5.9 and 12.76 km, respectively, and 75% of the modeled positions had errors less than 6.25 km and 11.7 km for each seal. Confidence interval coverage was close to correct at typical levels (80–95%), although it tended to be overly generous at smaller sizes. The reliability of uncertainty estimates was also affected by the chosen speed threshold. The combination of speed and Kalman filtering allows for effective calculation of location and also indicates the limits of accuracy when correcting service Argos locations and linking satellite telemetry data to spatial covariate and habitat data.

Erratum to: Induction and decay of short-term heat acclimation - Andrew T. Garrett; Niels G. Goosens; Nancy J. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2009)

Induction and decay of short-term heat acclimation - Andrew T. Garrett; Niels G. Goosens; Nancy G. Rehrer; Mark J. Patterson; James D. Cotter (European Journal of Applied Physiology, 2009)

Behaviour and physiology of sockeye salmon homing through coastal waters to a natal river - Glenn T. Crossin; Scott G. Hinch; Steven J. Cooke; David W. Welch; Sonia D. Batten; David A. Patterson; Glen Van Der Kraak; J. Mark Shrimpton; Anthony P. Farrell (Marine Biology, 2007)

Decibel Attenuation of Pulsed Electromagnetic Field (PEMF) in Blood and Cortical Bone Determined Experimentally and from the Theory of Ohmic Losses - Maciej Zborowski; Boris Kligman; Ronald J. Midura; Alan Wolfman; Thomas E. Patterson; Michael Ibiwoye; Mark Grabiner (Annals of Biomedical Engineering, 2006)

Possible role for the 5-HT1A receptor in the behavioral effects of REM sleep deprivation on free-operant avoidance responding in rat - Mark T. Harvey; Randy L. Smith; Michael E. May; Mary Caruso; Celeste Roberts; Tina G. Patterson; Maria Valdovinos; Craig H. Kennedy (Psychopharmacology, 2004)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

The reproducibility of closed-pouch sweat collection and thermoregulatory responses to exercise?heat stress - Gavin Hayden; Helen C. Milne; Mark J. Patterson; Myra A. Nimmo (European Journal of Applied Physiology, 2004)

Uncontrolled manifold analysis of single trials during multi-finger force production by persons with and without Down syndrome - John P. Scholz; Ning Kang; David Patterson; Mark L. Latash (Experimental Brain Research, 2003)

Magnetic Field Visualization in Applications to Pulsed Electromagnetic Field Stimulation of Tissues - Maciej Zborowski; Ronald J. Midura; Alan Wolfman; Thomas Patterson; Michael Ibiwoye; Yoshi Sakai; Mark Grabiner (Annals of Biomedical Engineering, 2003)

Finger coordination in persons with Down syndrome: atypical patterns of coordination and the effects of practice - Mark L. Latash; Ning Kang; David Patterson (Experimental Brain Research, 2002)

Effects of artificially-induced anaemia on sudomotor and cutaneous blood flow responses to heat stress - Nigel A. S. Taylor; Mark J. Patterson; James D. Cotter; Duncan J. Macfarlane (European Journal of Applied Physiology, 1997)

Sweat distribution before and after repeated heat exposure - James D. Cotter; Mark J. Patterson; Nigel A. S. Taylor (European Journal of Applied Physiology, 1997)

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 1. Insitu pumping rates - Mark R. Patterson; Valeri I. Chernykh; Vladimir A. Fialkov; Michael Savarese (Limnology and Oceanography, 1997)
Demosponges dominate the littoral zone of Lake Baikal, Russia. During August 1993, we measured the in situ pumping activity of a globose sponge, Baikalospongia bacillifera, common at depths of 8–50 m. Excurrent flow speed, surface area, and oscular diameter were measured with fluorescein dye release, underwater video, and image processing for nine individual sponges; diel deployments of a heated thermistor flowmeter were made on another three individuals. Mean pumping rates for oscula ranged from 0.2 to 3.3 cm s −1 , with instantaneous measurements as high as 25 cm s −1 . Although between‐sponge variability is large, oscula from an individual maintain speeds within 1 cm s −1 of each other. Volume fluxes for oscula measured from all individuals range from 0.01 to 0.60 cm 3 s −1 . Fluxes for individuals indicate that a sponge processes its volume in 17–24 s, comparable to values obtained for marine species. Oscula are not continuously active and often reduce pumping for several hours at irregular intervals. Two of three individuals monitored over a diel cycle exhibited negative correlations between the ambient current and oscular excurrent flow. Boundary layer measurements and diffusivity calculations demonstrate that sponges are capable of depleting picoplankton near the bottom.

Trophic effects of sponge feeding within Lake Baikal's littoral zone. 2. Sponge abundance, diet, feeding efficiency, and carbon flux - Adele J. Pile; Mark R. Patterson; Michael Savarese; Valeri I. Chernykh; Vladimir A. Fialkov (Limnology and Oceanography, 1997)
Endemic freshwater demosponges in the littoral zone of Lake Baikal, Russia, dominate the benthic biomass, covering 44% of the benthos. We measured in situ sponge abundance and grazing and calculated sponge‐mediated fluxes of picoplankton (plankton µ m) for two common species, Baikalospongia intermedia and Baikalospongia bacillifera. By means of dual‐beam flow cytometry, we found retention efficiencies ranging from 58 to 99% for four types of picoplankton: heterotrophic bacteria, Synechococcus‐type cyanobacteria, autotrophic picoplankton with one chloroplast, and autotrophic picoplankton with two chloroplasts. By using a general model for organism‐mediated fluxes, we conservatively estimate that through active suspension feeding, sponges are a sink for 1.97 g C d −1 m −2 , mostly from procaryotic cell types. Furthermore, grazing by these extensive sponge communities can create a layer of picoplankton‐depleted water overlying the benthic community in this unique lake.

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

A new RNA synthesis mutant of E. coli - David Patterson; Mark Weinstein; Sergio Marshall; David Gillespie (Biochemical Genetics, 1971)